Revolutionizing Pediatric Endodontics: A Review of Innovative Rotary Files (Academia Journal of Medicine, 2025)
Pediatric rotary files, designed for the endodontic treatment of primary and immature  teeth, have gained attention for their efficiency and safety. This review examines the  literature on various types of pediatric rotary files, highlighting their design features,  biocompatibility, and clinical outcomes. Studies indicate a reduced treatment time and  improved shaping ability compared to manual techniques. The review also discusses  the importance of selecting appropriate files based on tooth anatomy and the age of the  child. Overall, pediatric rotary files prove to be a promising tool in modern pediatric  dentistry, providing effective and minimally invasive treatment options.
Keywords: Pediatric Endodontics; Rotary Files; Pulpectomy